Analysis of The Labor Wage System Outsourcing Based on Islamic Economic Principles (Case Study Pt Dimas Perkasa Putra) - Lestari, Ira; Hamdani, Ikhwan; Hakiem, Hilman (Al-Infaq: Jurnal Ekonomi Islam, 2025)
This research aims to describe the labor wage system outsourcing based on an Islamic economic perspective. Furthermore, this research aims to analyze the labor wage system outsourcing at PT Dimas Perkasa Putra based on an Islamic Economics perspective. This research uses a qualitative descriptive approach by selecting secondary and primary data sourced from PT Dimas Perkasa Putra. The results of this research show that wages in Islam are called ijarah which is a transaction contract for the right to use certain goods or services as well as proportional payment of wages. In general, the wage system at PT. Dimas Perkasa Putra is in accordance with the Islamic economic perspective, where Islamic values are contained in the wage system at PT Dimas Perkasa Putra, namely aspects of feasibility and fairness, including being reviewed from the work agreement. In implementing the work agreement, PT Dimas Perkasa Putra has provided clarity for its workforce, especially regarding wages. The company emphasizes the suitability of the current wages for the workforce at PT Dimas Perkasa Putra to improve the quality of the company and the welfare of the workforce.